2019
DOI: 10.1093/neuros/nyz280
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluation of the Size Limitation in Single-Session Stereotactic Radiosurgery for Brain Arteriovenous Malformations: Detailed Analyses on the Outcomes with Focusing on Radiosurgical Doses

Abstract: BACKGROUND Single-session stereotactic radiosurgery (SRS) for large arteriovenous malformations (AVMs) ≥10 mL remains controversial, which is considered as the current size limitation. OBJECTIVE To reconsider the size limitation of SRS for AVMs by profoundly analyzing dose-volume relationship. METHODS Data on 610 consecutive patients with AVM treated with SRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…Benefits of embolization prior to SRS included reduced AVM volume allowing application of higher marginal dose and occlusion of associated aneurysms with a higher risk of bleeding. However, it also possibly results in some adverse effects like delayed recanalization and obscure nidus delineation 6,15 . Our analysis suggested that it was an independent factor reducing the nidus obliteration rate with an HR of 0.65, indicating that the probability of obliteration was dropped by 35% for AVMs who were previously embolized before SRS and consistent with a previous meta‐analysis investigating the efficacy of SRS in embolized AVMs 24 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Benefits of embolization prior to SRS included reduced AVM volume allowing application of higher marginal dose and occlusion of associated aneurysms with a higher risk of bleeding. However, it also possibly results in some adverse effects like delayed recanalization and obscure nidus delineation 6,15 . Our analysis suggested that it was an independent factor reducing the nidus obliteration rate with an HR of 0.65, indicating that the probability of obliteration was dropped by 35% for AVMs who were previously embolized before SRS and consistent with a previous meta‐analysis investigating the efficacy of SRS in embolized AVMs 24 .…”
Section: Discussionsupporting
confidence: 87%
“…Pooled estimates showed no significant and independent correlation between male sex and total obliteration by univariate analysis based on five studies (Fig. 3(a)), and by multivariate analysis based on two papers 6,16 . Regarding patient age, according to nine articles involving 3489 subjects with the median/mean age ranging from 22 to 42, no significant relationship between age and AVM obliteration was shown with univariate analysis (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Large AVMs are challenging targets. Radiosurgical doses are generally reduced for fear of RAEs, which in turn could decrease the obliteration rate and might eventually result in a higher hemorrhage rate 80. In short, it is important to balance the therapeutic effect and risks.…”
Section: Gkrs For Arteriovenous Malformationmentioning
confidence: 99%